Longitudinal single cell profiling of epitope specific memory CD4+ T cell responses to recombinant zoster vaccine - Xiaomin Wen; Alex K. Hu; Scott R. Presnell; Emily S. Ford; David M. Koelle; William W. Kwok (Nature Communications)
Abstract Vaccination leads to rapid expansion of antigen-specific T cells within in the first few days. However, understanding of transcriptomic changes and fates of antigen-specific T cells upon vaccination remains limited. Here, we investigate the fate of memory CD4+ T cells upon reactivation to recombinant zoster vaccine for shingles at cellular and transcriptional levels. We show that glycoprotein E-specific memory CD4+ T cells respond strongly, their frequencies remain high, and they retain markers of cell activation one year following vaccination. Memory T cells with the most dominant TCR clonotype pre-vaccination remain prevalent at year one post-vaccination. These data implicate a major role for pre-existing memory T cells in perpetuating immune repertoires upon re-encountering cognate antigens. Differential gene expression indicates that cells post-vaccination are distinct from cells at baseline, suggesting committed memory T cells display transcriptional changes upon vaccination that could alter their responses against cognate immunogens.